Dapagliflozin reverses the imbalance of T helper 17 and T regulatory cells by inhibiting SGK1 in a mouse model of diabetic kidney disease. Issue 5 (1st May 2021) - Wang, Dan; Zhang, Zikun; Si, Zekun; Yang, Yanlin; Li, Shuangshuang; Xue, Yaoming
Abstract : An imbalance between T helper 17 (Th17) and T regulatory (Treg) cell subsets contributes to the pathogenesis of diabetic kidney disease (DKD). However, the underlying regulatory mechanisms that cause this imbalance are unknown. Serum/glucocorticoid‐regulated kinase 1 (SGK1) has been suggested to affect Th17 polarization in a salt‐dependent manner, and sodium/glucose cotransporter 2 inhibitors (SGLT2i) have been demonstrated to regulate sodium‐mediated transportation in the renal tubules. This study aimed to evaluate the potential benefits of dapagliflozin (Dap) on DKD, as well as its influence on shifting renal T‐cell polarization and related cytokine secretion. We treated male db/db mice with Dap or voglibose (Vog) and measured blood and kidney levels of Th17 and Treg cells using flow cytometry. We found that Th17 cells were significantly increased, while Treg cells were significantly decreased in diabetic mice. Moreover, Dap suppressed the polarization of Th17/Treg cells by inhibiting SGK1 in diabetic kidneys, and this was accompanied by attenuation of albuminuria and tubulointerstitial fibrosis independent of glycemic control. Taken together, these results demonstrate that the imbalance of Th17/Treg cells plays an important role in the progression of DKD. Moreover, Dap protects against DKD by inhibiting SGK1 and reversing the T‐cell imbalance. Abstract : An imbalance between Th17 and Treg cell subsets contributes to the pathogenesis of diabetic kidney disease. We found that Th17 cells were increased, while Treg cells were decreased in diabetic mice. Dapagliflozin suppressed the polarization of Th17/Treg cells by inhibiting SGK1 in diabetic kidneys, and this was accompanied by attenuation of albuminuria and tubulointerstitial fibrosis independent of glycemic control.